EXTRACTION, STABILITY AND SEPARATION OF ANTHOCYANINS OF IXORA COCCINEA LINN - Patil, Nital; Datar, Ajit (International Journal of Pharmacy and Pharmaceutical Sciences, 2015)
Objective: In the present study, a new, simple and an efficient microwave oven extraction method was developed for maximum yield of colorant from Ixora coccinea flowers. The preliminary stability study of colorant was carried out to provide reliable data for application of the plant. Methods: The comparison of cold extraction and microwave oven extraction method was carried out. The crude anthocyanin content was estimated by using pH differential method. The stability of color extract was evaluated for the period of one month by using UV- Visible spectroscopy. An attempt was made to separate color components of the extract by developing HPTLC method. Results: The yield of microwave oven extraction of colorant is found to be 13.26% under the optimized conditions set at the temperature of 70ËšC, 50 minutes time, 0.1% HCl concentration in solvent and 1:60 ratio of sample to solvent. The result indicated that the anthocyanin content is 704.73 mg/100 g to 662.79 mg/100g in fresh material. The study demonstrated that the pinkish red extract of the flowers is stable under low pH values (â‰¤4) and unstable under alkaline conditions. It is also found to be sensitive to high temperature and light. The HPTLC profile of color showed the presence of pink and violet color major components at Rf values 0.17, 0.33, 0.37, 0.56, 0.67 and 0.83. Conclusion: The experimental work on Ixora coccinea provides enough information to tap its potential as a colorant in acidic foods or cosmetics. Â